2011
DOI: 10.1002/anie.201105314
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic Liquid Crystals as Templates for Anisotropic Growth of Nanoparticles

Abstract: Control over size, shape, and composition of nanomaterials is one of the major concerns in the field of nanoscience today. This task has induced a tremendous amount of work, in which methods based on chemical or physical processes were developed to synthesize such nanosystems. Among the various strategies, organic molecules and macromolecules, exhibiting an anisotropic shape or a particular organization, have been used as templates for controlling the shape and size of inorganic materials.[1] Literature reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Usually the aggregation of semiconductor NCs results in the formation of photoinactive structures due to the abolitiono fq uantum confinement within particles larger than over ad ozen nanometers. In contrast to the previously reported data, [10,11] we faced an apparent paradox, that is, the photoactivity was preserved despite the formation of aggregates. Twop ossible explanations were considered:1 )the NCs were squeezed/interdigitate together during compression to form aggregates, but without coalescence of the cores;2 )water molecules hydrolyzed the bonds between the ZnO cores and ligand molecules.W ithoutt he organic shell,t he ZnO cores coalescedd ue to high surface energy.T he observedt urbidityo f the film appeared upon the formation of macroscopicZ nO, which was not photoactive and did not influence the emission spectra.Because the process was restricted by the geometry of the system not all the NCs aggregated.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Usually the aggregation of semiconductor NCs results in the formation of photoinactive structures due to the abolitiono fq uantum confinement within particles larger than over ad ozen nanometers. In contrast to the previously reported data, [10,11] we faced an apparent paradox, that is, the photoactivity was preserved despite the formation of aggregates. Twop ossible explanations were considered:1 )the NCs were squeezed/interdigitate together during compression to form aggregates, but without coalescence of the cores;2 )water molecules hydrolyzed the bonds between the ZnO cores and ligand molecules.W ithoutt he organic shell,t he ZnO cores coalescedd ue to high surface energy.T he observedt urbidityo f the film appeared upon the formation of macroscopicZ nO, which was not photoactive and did not influence the emission spectra.Because the process was restricted by the geometry of the system not all the NCs aggregated.…”
Section: Resultscontrasting
confidence: 99%
“…[9] Only very recently,K ahn and co-workers reported the first successful hybridization of liquid-crystalline molecules with small-sizedZ nO NCs [10] and the use of aL C system as at emplating agent for the preparation of ZnO NCs. [11] Notably,t he passivating LC systemsi na ll the abovementioned cases act as aL -type neutrall igand. [12] To the best of our knowledge,t here is only one example of an effective modification of ZnO NC surfaces by aX -type liquid-crystalline ligand,w hich was obtained by using al igand-exchange reaction andg raftingm esogenic units aroundt he ZnO NC cores.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, small (<6 nm) isotropic ZnO NPs are formed at higher temperatures, as local order is disturbed throughout the liquid crystal. 216 Considering reactions in air, it is useful to determine the oxygen source, which could be H2O or O2. While hydrolysis of MLx (L = R or NR2) cleanly generates M−OHx and L−H (x equiv.…”
Section: Hydrolysis Routes To Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…[9,[12][13][14] For severaly ears, we have developed the preparation of metalo xide NPs taking advantage of the exothermic hydrolysis reactiono fo rganometallic precursors to get, in one step and underm ild conditions (room temperature and atmospheric pressure), well-definedc rystalline metal oxide NPs. [19,20] Herein, to gain further insights aboutt he NPs growth mechanism withouts olventi nt he presence of fatty amine, we have investigated the effect of the temperature and composition upon the morphologyo fZ nO NPs and upon the structural and optical properties of the obtained hybrid materials.A ss tated above, the synthesiso fZ nO NPs studied herei sv ery simple and involved just fattya mines. eitheri sotropic NPs or nanorods) has been achievedb yv arying the experimental conditions:i sotropic NPs are obtainedi nt he presence of alkyl chain amine ligandsi na no rganic solvent while nanorods are obtained under the same experimental conditions but in the absence of solvent.…”
mentioning
confidence: 99%
“…[17,18] Moreover,a tam acroscopic scale, we demonstrated that the use of an ematic phaseo btained from at hermotropicl iquid-crystalline compound can serve as template for anisotropic growth of ZnO NPs and that hybrid NPs/LC materials can be obtained. [19,20] Herein, to gain further insights aboutt he NPs growth mechanism withouts olventi nt he presence of fatty amine, we have investigated the effect of the temperature and composition upon the morphologyo fZ nO NPs and upon the structural and optical properties of the obtained hybrid materials.A ss tated above, the synthesiso fZ nO NPs studied herei sv ery simple and involved just fattya mines. [20] In at ypical experiment, the dicyclohexyl zinc precursor,[ Zn(cy) 2 ], is mixeda tr oom temperature with two equivalents of hexadecylamine( HDA)a st he ligand; no solvent was used.…”
mentioning
confidence: 99%